Studies on immunological paralysis. II. The detection and significance of antibody-forming cells in the spleen during immunological paralysis with type III pneumococcal polysaccharide - Howard, J. G. (1969)
The immunocytoadherence (rosette) technique has been adapted to study the immune response to varying doses of type III pneumococcal polysaccharide (SIII). Syngeneic erythrocytes coated with SIII were incubated with washed spleen cell suspensions isolated 0·5–39 days after i.v. injection into CBA strain mice of immunogenic (0·5 or 5·0 μg) or paralysing (500 μg) doses of SIII; the immunizing or paralysing effect of these doses of SIII was confirmed by a passive haemagglutination technique. The number of rosette-forming cells per spleen was significantly increased above the background range in twenty-seven out of forty-two, twenty-four out of thirty-seven and forty-one out of forty-six animals injected with 0·5, 5·0 and 500 μg SIII, respectively. Not only was there a greater incidence of `positive' values in the paralysed group, but the response was better maintained than in the immunized groups. In view of the apparent lack of central inhibition in these experiments, paralysis with SIII was considered to be attributable to the antibody-neutralizing effect of persisting undegraded antigen. It is suggested that the phenomenon of polysaccharide paralysis may be the expression of more than one mechanism.